The Relationship Between TSH and Indirect Bilirubin Levels in Neonates Suspected of Having Jaundice - Nur Alizah; Anik Handayati; Museyaroh Museyaroh; Suhariyadi Suhariyadi (Knowledge Dynamics, 2024)
Background: Congenital hypothyroidism (CH) is a condition of thyroid hormone deficiency that occurs at birth. The TSH (thyroid-stimulating hormone) test is crucial for diagnosing hypothyroidism. CH is known to cause prolonged unconjugated hyperbilirubinemia. Therefore, this study aimed to analyze the relationship between TSH and indirect bilirubin levels in neonates suspected of having jaundice. Methods: This is a non-experimental, retrospective study conducted at Lombok Dua Dua Lontar Mother and Child Hospital in Surabaya. The study involved data collection on neonates aged 2–7 days suspected of jaundice, whose TSH and indirect bilirubin levels were measured between November 2022 to April 2024. Results: Among 100 neonates, 62% were aged 2-4 days, while 38% were aged 5-7 days. The majority were male (56%), with female comprising 44%. Of the 100 neonates, only 1 (1%) had borderline TSH levels, while 99% had normal TSH levels. Hyperbilirubinemia was observed in 94% of the neonates, while 6% had normal indirect bilirubin levels. Statistical analysis using the Spearman correlation showed no significant link between TSH and indirect bilirubin levels (p = 0.802). Conclusions: While this study did not find a clear connection between TSH and indirect bilirubin levels in neonates suspected of having jaundice, one case of borderline TSH was identified. This neonate required referral to pediatric endocrinology, as untreated congenital hypothyroidism can lead to mental retardation. Despite limited research linking TSH and bilirubin levels in jaundiced neonates, routine screening for congenital hypothyroidism using TSH testing should be reconsidered. Future studies could benefit from focusing on specific causes of neonatal jaundice to help narrow down research questions in this area.